2022
DOI: 10.1186/s12864-022-08446-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nuclear matrix attachment regions during 5th instar posterior silk gland development in Bombyx mori

Abstract: Background Chromatin architecture is critical for gene expression during development. Matrix attachment regions (MARs) control and regulate chromatin dynamics. The position of MARs in the genome determines the expression of genes in the organism. In this study, we set out to elucidate how MARs temporally regulate the expression of the fibroin heavy chain (FIBH) gene during development. We addressed this by identifying MARs and studying their distribution and differentiation, in the posterior si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Only two studies of genome-wide mapping of S/MAR investigate their dynamics during embryonic development or cellular differentiation ( Chunduri et al, 2022 ; Sureka et al, 2022 ). These studies, for the first time, uncovered that these attachment points can be categorized as dynamic or stable (Core-MARs) ( Figure 1 ).…”
Section: Genome-wide Distribution Of S/mars: Dynamic and Constitutive...mentioning
confidence: 99%
“…Only two studies of genome-wide mapping of S/MAR investigate their dynamics during embryonic development or cellular differentiation ( Chunduri et al, 2022 ; Sureka et al, 2022 ). These studies, for the first time, uncovered that these attachment points can be categorized as dynamic or stable (Core-MARs) ( Figure 1 ).…”
Section: Genome-wide Distribution Of S/mars: Dynamic and Constitutive...mentioning
confidence: 99%
“…Cyclins B and E and Scr have been shown to be involved in this process [17,18]. In the larval stage, the silk gland no longer undergoes mitosis and increases its DNA content only through intranuclear replication [19,20]; it has been shown that Let7 MicroRNAs (Let7) knockout promotes intranuclear replication in silk gland cells [21,22]. Apoptosis in the silk gland is thought to be regulated by ecdysteroids (insect growth and molting hormones) and involves both apoptosis and autophagy [23][24][25].…”
Section: Introductionmentioning
confidence: 99%